Congress of the Spanish Language in Cádiz - E. A. Klochko (Ибероамериканские тетради, 2023)
More than 300 scholars and experts from the Spanish-speaking world took part in the IX International Congress of the Spanish Language held in Cádiz from 27 to 30 March 2023. Special attention was paid to the indigenous languages of Latin America and the Caribbean. The participants emphasized the importance of preserving the languages and traditions of indigenous nations of the region, which contributes to the preservation of cultural heritage and strengthens the relationship between Spain and Latin America. During the Congress, the emergence of such phenomena as Spanglish and Portuñol and linguistic perspectives in the era of artificial intelligence and social media were discussed. The scholars emphasized an indisputable role of the Spanish language in uniting cultures and peoples on both sides of the Atlantic.